(untitled) (Aporte Santiaguino, 2024)
The diversity of arthropods presents in Aptenia cordifolia (L.f) Schwantes was analyzed, based on species richness, abundance and trophic roles, in the green areas of the National Agrarian University La Molina (UNALM), in the district of La Molina, province of La Molina, Lima Region, with the coordinates 12°04′55″ South Latitude, 76°56′53″ West Longitude at 251 meters above sea level. It was evaluated once a week from September 2018 to February 2019, noting the arthropod population and the surrounding plants one meter away. The samples were duly identified and preserved; they are identified in a stereoscope at the UNALM Museum of Entomology. At each evaluation point an area of 0.25m x 0.25m is examined. In total, 74,017 arthropods were collected distributed in the class Arachnida (one order and one family) and Insecta (six orders and 14 families). According to the functional group, phytophages are comprised of ten species, predator with five, pollinator, parasitoid and varied feeding with one species. In addition, the following were categorized as the most important pest insects according to occurrence: Pulvinaria psidii Maskell, Pseudococcus longispinus (Targioni-Tozzetti), Saissetia coffeae (Walker), Platynota sp. and as the main natural enemy Scymnobius sp.